IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE PRINCIPLES IN PT. X AS A TRANSPORT SERVICE COMPANY JAKARTA - KALIMANTAN - Ersa Rahmadania, Silvia (Dinasti International Journal of Management Science, 2020)
With so many companies that have emerged and can evolve over time, now the family company has experienced rapid progress. This article was created with the aim of being able to discuss the application of the principles of Good Corporate Governance in family businesses. PT. X which is engaged in heavy equipment transportation services and has two offices in different regions. By using descriptive qualitative analysis methods in order to provide good information and understand the principles of Good Corporate Governance. Based on the results of the study it can be concluded that PT. X must face problems in the application of the principle of corporate accountability is still not able to apply the job desk properly so that in the implementation of the job desk that is implemented still does not meet the principle of independence. So the company is expected to be able to better organize the organizational structure and by using the Family Owned Enterprise (FOE) family company so that the principles of Good Corporate Governance can be better applied to the company.